Clinical importance of portal venous gas detected by abdominal sonography - Gregorič, Primož (Radiology and oncology (Ljubljana), 2004)
Background. Portal venous gas (PVG) can be a sign of serious disease and a predictor of poor clinical outcome. However, it ean also occur as a transient phenomenon with little clinical significance, especially following blunt abdominal trauma and various diagnostic and therapeutic procedures. Case reports. We describe two patients with PVG detected on abdominal sonography, who had very similar sonographic findings but a completely different clinical outcome. The first patient was a 70-year-old man in whom PVG was the consequence of mesenteric infarction; the patient died in hospital shortly after the admission. Our second patient was a 26-year-old man who was injured in a motor vehicle accident. He was clinically stable and needed no aggressivetreatment. PVG proved to be a transient phenomenon that cleared spontaneously within a day. Conclusions. Doppler sonography is a sensitive andspecific modality for the detection of PVG. In patients with a serious underlying disease, sonography can identify the cause of PVG, so that the appropriate therapy may be undertaken without delay. If the aetiology is unclear, the decision to undertake further expensive and potentially harmful diagnostic procedures should be based on the patient's clinical status.
Keywords: Aged; diagnostika; Embolija zračna; Embolism, Air; Portal Vein; Portalna vena; Starostniki; Ultrasonografija dopplerska; Ultrasonography; Ultrasonography, Doppler; ultrazvočna diagnostika